Simulations of backgate sandwich nanowire MOSFETs with improved device performance - 赵恒亮 朱慧珑 钟健 马小龙 魏星 赵超 陈大鹏 叶甜春 (Journal of semiconductors, 2014)
We propose a novel backgate sandwich nanowire MOSFET （SNFET）, which offers the advantages of ETSOI （dynamic backgate voltage controllability） and nanowire FETs （good short channel effect）. A backgate is used for threshold voltage （Vt） control of the SNFET. Compared with a backgate FinFET with a punch-through stop layer （PTSL）, the SNFET possesses improved device performance. 3D device simulations indicate that the SNFET has a three times larger overdrive current, a -75% smaller off leakage current, and reduced subthreshold swing （SS） and DIBL than those of a backgate FinFET when the nanowire （NW） and the fin are of equal width. A new process flow to fabricate the backgate SNFET is also proposed in this work. Our analytical model suggests that Vt control by the backgate can be attributed to the capacitances formed by the frontgate, NW, and backgate. The SNFET devices are compatible with the latest state-of-the-art high-k/metal gate CMOS technology with the unique capability of independent backgate control for nFETs and pFETs, which is promising for sub-22 nm scaling down.